Pressure-dependent constitutive and failure model for laminated composites - Pinho,ST; Robinson,P; Schuecker,C; Camanho,PP (2009)
This paper presents a non-linear, pressure-dependent, three dimensional constitutive law and associated failure criteria for laminated composites with UD plies. The failure criteria result from a physical model for each failure mode. In-situ strengths are used for matrix failure and fibre kinking. The model is validated against experimental data.